2016
DOI: 10.1038/cddis.2016.363
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of Ccr2 alleviates photoreceptor cell death in rodent retina exposed to chronic blue light

Abstract: Age-related macular degeneration (AMD), the leading cause of visual loss after the age of 60 years, is a degenerative retinal disease involving a variety of environmental and hereditary factors. Although it has been implicated that immune system is involved in the disease progression, the exact role that microglia has is still unclear. Here we demonstrated that knockout of Ccr2 gene could alleviate photoreceptor cell death in mice retinas exposed to chronic blue light. In Ccr2−/− mice, a damaged microglia recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 56 publications
0
26
1
Order By: Relevance
“…Thus, despite the large, transient increase in CCL2 expression by Müller cells and evidence that blocking the CCL2-CCR2 signaling reduced the influx of CD45 high cells, neurodegeneration proceeded unabated. Unlike other retinal damage studies in which monocytes exacerbate degeneration [14,37,38], our results demonstrate that monocyte infiltration does not necessarily further harm or control the rate of neurodegeneration.…”
Section: Eliminating Ccl2-ccr2 Signaling Did Not Alter the Rate Of Recontrasting
confidence: 88%
See 1 more Smart Citation
“…Thus, despite the large, transient increase in CCL2 expression by Müller cells and evidence that blocking the CCL2-CCR2 signaling reduced the influx of CD45 high cells, neurodegeneration proceeded unabated. Unlike other retinal damage studies in which monocytes exacerbate degeneration [14,37,38], our results demonstrate that monocyte infiltration does not necessarily further harm or control the rate of neurodegeneration.…”
Section: Eliminating Ccl2-ccr2 Signaling Did Not Alter the Rate Of Recontrasting
confidence: 88%
“…The loss of photoreceptors in Arr1 −/− mice occurs at light levels that do not cause photolytic damage (75-200 lx, undilated pupils of pigmented mice) or stress the regenerative capacity of the RPE, at least at the early times being considered in this study. This is in contrast to studies that inflicted broader damage, such as Rutar and colleagues [37], who suppressed retinal CCL2 levels with small interfering RNA (siRNA) and found a reduced the number of apoptotic photoreceptors induced by bright light (1000 lx, dilated pupils); Sennlaub and colleagues [14] who knocked out CCL2 and rescued photoreceptor degeneration caused by light stress (4500 lx, dilated pupils); or Hu and colleagues [38] who knocked out CCR2 and found significant structural and functional preservation of the retina after exposure to blue light-induced damage (500 lx, daily for 3 days). The exclusive damage to photoreceptors is presumably why CCL2 is one of only a handful of cytokines that change in the Arr1 −/− at early times ( Fig.…”
Section: Neurodegeneration Proceeds Independent Of Monocyte Recruitmentmentioning
confidence: 61%
“…Release of the biologically active IL-1b requires the expression and activation of inflammasome complex, among which the most well-documented one is NLRP3. Activation of the NLRP3 inflammasome complex appears to be dependent on types of cells involved and is effected by a diverse range of stimuli, including microbe-derived products (54), environmental factors (55), and endogenous molecules (56). Reports have indicated that the NLRP3 inflammasome confers protection against L. amazonensis infection in resistant C57BL/6 mice (57), whereas L. major and L. mexicana could significantly inhibit NLRP3 inflammasome function and IL-1b production (58).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, rats receiving intravitreal injection of CCL2 siRNA showed a markedly decreased phagocyte accumulation and photoreceptor apoptosis after light damage (Rutar et al, ). Similarly, CCR2 knockout mice had much lower photoreceptor demise after chronic blue light exposure (Hu et al, ), less pro‐inflammatory cells and CNV in the laser‐damage model (Robbie et al, ), and fewer subretinal macrophages when immunized with carboxyethylpyrrole‐modified albumin as trigger for oxidative stress (Cruz‐Guilloty et al, ).…”
Section: Targeting Mononuclear Phagocytes In Retinal Degenerative Dismentioning
confidence: 99%